Does Euro-English have native speakers? Making sense of conflicting views - Gozdawa-Gołębiowski, Romuald (Studies in Second Language Learning and Teaching, 2012)
This paper examines the status of European English (EE) in current linguistic theory, in particular the hotly debated issue of whether or not it is possible to treat EE as an endonormative linguistic variety in its own right. Alternatively, EE may remain a form of English as a foreign language (EFL), and the decision has far-reaching socio-political consequences. Some relevant data from Polish English is discussed in this context. It is argued that there is no reason to reanalyse the observed deviations from English native standards as simplifications or innovations characteristic of a new language. The debate is shown to relate to the opposition between utilitarian and epistemic goals in foreign language teaching methodology, as exemplified by the dichotomy between competence and performance or between training for interaction and training of the faculties of the mind.